2017
DOI: 10.1021/acssynbio.7b00112
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Programmable Protein Mutagenesis Using Plasmid Recombineering

Abstract: Comprehensive and programmable protein mutagenesis is critical for understanding structure-function relationships and improving protein function. However, current techniques enabling comprehensive protein mutagenesis are based on PCR and require in vitro reactions involving specialized protocols and reagents. This has complicated efforts to rapidly and reliably produce desired comprehensive protein libraries. Here we demonstrate that plasmid recombineering is a simple and robust in vivo method for the generati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Earlier studies focused on the effects of mutating the conserved cysteine, which forms a covalent bond with the flavonoid cofactor during the photocycle, and some random mutations on flavin binding and photochemical reactivity [55,56]. Later studies probed the effects of mutations on other properties, particularly the absorption spectrum [47,50,57,58], photocycle lifetime [57,59], brightness of the cysteine-less variants [9,19,20,60], generation of radicals [15,61,62] and thermal stability [21][22][23]. Many of these mutations were rational, or could be rationalized after initial discovery, thus allowing one to apply the same principles to impart a different LOV domain with the desirable properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies focused on the effects of mutating the conserved cysteine, which forms a covalent bond with the flavonoid cofactor during the photocycle, and some random mutations on flavin binding and photochemical reactivity [55,56]. Later studies probed the effects of mutations on other properties, particularly the absorption spectrum [47,50,57,58], photocycle lifetime [57,59], brightness of the cysteine-less variants [9,19,20,60], generation of radicals [15,61,62] and thermal stability [21][22][23]. Many of these mutations were rational, or could be rationalized after initial discovery, thus allowing one to apply the same principles to impart a different LOV domain with the desirable properties.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the effects of the proline substitutions may also be transferable to other LOV domains, since the rationales that we employed (consensus design [26][27][28], stabilization by prolines [27,28]) will hold. Interestingly, out of three LOV domain thermal stabilization studies [21][22][23], only one reported the proline substitutions [22], which were, however, not included in the most stable variant with multiple mutations. Thus, testing the effects of proline substitutions may be a complementary approach to recombination, and directed evolution to speed up the discovery of the most stable variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an iterative recombineering approach called SIRCAS (stepwise integration of rolling circle amplified segments) [64], the Salmonella typhimurium genome was extensively modified in the largest genomic recoding effort to date, enabling 1557 synonymous leucine substitutions. In addition to whole genome mutagenesis through recombineering, the flexibility of this oligo-based approach was recently demonstrated in strategy that extended its applications to directed protein evolution [65]. As a proof of concept, the authors used plasmid recombineering to subject the 110-residue iLOV protein to saturation mutagenesis with near complete coverage (99.8% of all mutations), uncovering many variants with improved thermostability.…”
Section: Mutagenesis Methods For Genome Engineering and Genome-wide Smentioning
confidence: 99%
“…violacein [38,44,45]) and proteins [46][47][48][49], as well as by genome-wide codon replacement to create a so-called "genomically recoded organism" (GRO) engineered to depend on synthetic amino acids [50][51][52], MAGE has paved the way for previously unimaginable evolutionary innovations.…”
Section: Multiplex Automated Genome Engineeringmentioning
confidence: 99%